Eccentricity Based Topological Indices of Some Benzenoid Structures - Iqbal, Hifza; Ahmad, Muhammad Ozair; Ali, Kashif; Rizvi, Syed Tahir Raza (Utilitas Mathematica, 2020)
Various topological parameters are employed to calculate the bioactivity of different chemical structures. Therefore, helping the researchers to make up for the shortage of laboratory experiments and can provide theoretical ground for the manufacturing of chemical products. Connectivity based topological indices have eminent role in the field of chemistry. In this paper, we study average eccentricity, eccentric connectivity index, first eccentric Zagreb index and eccentricity based geometric arithmetic index for the molecular structure of zig zag Benzenoid and the molecular structure of rhombic Benzenoid. Furthermore, we give analytically closed formulas for these indices which will be helpful in studying the underlying topologies. © 2020 Utilitas Mathematica Publishing Inc.. All rights reserved.